ESTUDO DE NEOPLASMAS MAMÁRIOS EM CÃES - Sereno, Beatriz Zanfra; Ziegler, Simoní Janaína; Pizutti, André Lucca; Alves, Ramão Felipe De Marques; Inkelmann, Maria Andréia (Salão do Conhecimento, 2018)
PROJETO DE PESQUISA REALIZADO NO CURSO DE MEDICINA VETERINÁRIA DA UNIJUÍ